A Survey on Anticoagulation Practices in Patients with Chronic Kidney Disease in Saudi Arabia - Mansoor Radwi; Enad Alsolami (Journal of Clinical Medicine, 2026)
Background/Objectives: Anticoagulation in advanced chronic kidney disease (CKD) remains challenging due to limited representation in clinical trials, resulting in uncertainty regarding optimal drug selection, dosing, and monitoring strategies. Methods: We conducted a cross-sectional, web-based survey of clinicians involved in CKD care and anticoagulation prescribing. The questionnaire explored respondent characteristics, methods of renal function estimation, anticoagulant selection across common CKD scenarios, anticoagulants’ dosing and monitoring practices, and approaches to anticoagulation in nephrotic syndrome. Results: Fifty-seven clinicians participated in the survey. Unfractionated heparin was the preferred agent for venous thromboembolism (VTE) prophylaxis in patients with stage 4 and 5 CKD, or on dialysis. For acute VTE treatment, anticoagulant choice varied by CKD severity, with unfractionated heparin, direct oral anticoagulants (DOACs), and low-molecular-weight heparin (LMWH) all reported to be used depending on stages of CKD. Warfarin and DOACs were commonly used for treatment of chronic VTE and atrial fibrillation (AF), with warfarin more frequently selected in patients receiving dialysis. Apixaban was the most frequently reported DOAC, typically at a dose of 2.5 mg twice daily in advanced CKD and dialysis. Renal function estimation methods varied, with Cockcroft–Gault most used overall, while nephrologists more frequently reported MDRD or CKD-EPI equations. Most respondents reported not routinely monitoring DOAC levels, and the majority indicated the absence of a structured multidisciplinary team (MDT) for managing anticoagulated CKD patients. Clinical practice varied according to specialty, experience, and healthcare setting, particularly in anticoagulant selection, dosing strategies, and use of risk stratification tools. Conclusions: Anticoagulation practices in advanced CKD are highly heterogeneous, reflecting persistent evidence gaps. While unfractionated heparin and warfarin remain central in patients with stage 5 CKD or on dialysis, DOAC use—particularly apixaban—has expanded, often with empiric dose reduction. These findings underscore the need for clearer guidance, standardized approaches to renal function assessment, multidisciplinary care pathways, and prospective studies focusing on anticoagulation use in CKD populations.